How state mobilised the aspects of politics, economy and culture to make people more national - Lee, Pei May; Lau, Zhe Wei (Universiti Malaysia Sarawak, 2013)
Nationalism is an important element which can allow the state to make its ruling legitimate, thus enabling it to retain power for long. Nationalism itself is a sense of belonging beyond the geographical landscape. The nationalism a person has may not necessary be for the state he or she is accorded with citizenship, but it can be for his or her country of origin and vice versa. Since the nationalism of a person is not fixed and is fluctuated according to the period of time depending on the needs and the interest of that time, state can often shaped nationalism the way it wants it to be particularly with the help of the appropriate machineries it owned. The state often employs politic, economy and culture means to make people more national. In terms of politics, state tends to spread propaganda to insert fear and the importance of unity within the nation. The state rallies the support of the people to stand up against the external threats. Culture is one of the most workable elements to instil nationalism in the mind of the people. State will promote their national identity through their heritage cultures and everyday life. For instance, in country such as Japan, the state equalise their self-discipline as their national identity which is far better than the West. The same argument goes for the economy aspect. The mode of economy is being implemented by showing the speciality and strength of their economy in their own words.